Stimulating Children's Independence from an Early Age Through Semada Activities - faizah, Khoirul; Ismaiyah, Nurul; Hotiati, St.; Muammaroh, Faiqotul; Aini, Selfi Yatul; Sa'diyah, Halimatus (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This study examines the effectiveness of the SEMADA (One Day Night at RA Asy-Syuhada’ program in stimulating early childhood independence. The type of research uses a classroom astion research method, data were collected through systematic observation, steuctured interviews and comprehensive documentation of 72 students divided into four groups. The SEMADA program is a overnight activity at school with teacher assistance without the presence of parents which is carried out in a structured manner with a series of activities that have been designed. The implementation of the program includes the preparation, implementation, and evaluation phases with a focus on developing aspects of independence in daily activities. The results of the study showed a significant increase in indicators of child independence, including the ability to carry out personal activities, simple decision making, and emotional management. These finding indicate that the SEMADA program is effective as a strategy for stimulating early childhood independence in the context of formal education, especially in early childhood education.